Performance Evaluation Of Orthogonal Frequency Division Multiplixing Systems Over Indoor Multipath Fading Channels - Abdo Saeed, Mohammed (2003)
High-data-rate communications are limited not only by noise but often more significantly by the intersymbol interference (lSI) which arises due to the memory of the dispersive multipath fading channels. The aim of this thesis is to investigate the performance of the Orthogonal Frequency Division Multiplexing (OFDM) scheme over wideband multipath fading channels. OFDM is a technique that can be used for transmitting data at extremely high rates by means of splitting up the serial data stream into several parallel streams which are transmitted simultaneously on different subcarriers, each occupying a small fraction of the available bandwidth. By inserting guard interval that is longer than the delay spread of the channel between the OFDM symbols, the lSI can be mitigated or totally eliminated.In this thesis, the theoretical description and modeling of dispersive multipath fading channels is presented. A proposed channel model based on Saleh and Valenzuela model is introduced and implemented by computer simulation. The bit-error-rate (BER) performance of the uncoded OFDM system, in terms of energy per bit-to noise ratio (EBNR), is investigated by simulations for different modulation schemes with both coherent and differential detection. The influence of the number of carriers as well as the guard interval duration on the performance is also investigated. We observed that the EBNR required to achieve a certain BER is significantly increased by 8 - 1 0 dB for dense multipath fading channels over that required in additive white Gaussian noise (AWGN) channels due to the decrease of the signal power as a result of increasing the number of paths. In addition, differential modulation improves performance in environments where rapid changes in phase are possible. OFDM can be implemented equally well with coherent (non-differential) modulation and demodulation to maximize the signal-to-noise ratio performance of the system. These performance measures are useful for the design and assessment of high speed indoor wireless communication systems.